PEMBELAJARAN TEMATIK DI KELAS 4, 5 DAN 6 DI SD MUHAMMADIYAH KOTA MALANG DAN KEC. LAWANG - Marhan Taufik; Dyah Worowirastri Ekowati; Agung Deddiliawan I. (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2015)
The activities "IbM for Thematic TeacherIn SD Muhammadiyah" isone of theanswers to some ofthe problems that existin SD Muhammadiyah Malang 5 and SD Muhammadiyah 6 Lawang.Activitiesarecarried outbya team ofstewardsof thisteamisa continuation of previous programs implementedingrades 1-3. In 2014, the activitiesongrades 4-6, aimtoprovidea greaterbenefitto theschool, andencouragedirectparticipation ofthe school community (teachers, students, principals, employees) andthe communitytoimprove thequality of schools.Particularlyintheimplementation ofthematic learningingrades 4-6.In practice, this programwas precededbya workshop onthematic learningfollowed byfacilitationof makingnetstheme, lesson plansandsyllabithematic learning, thematic learningpracticesin the form ofpeer teaching, as well as thereview andrevision ofthe netstheme, lesson plansandsyllabithematic learning. This activityinvolvescooperationwithschools/SDpartners. There aretwoschoolsinvolvedinthisactivity, namely SDMuhammadiyahMalang5andSDMuhammadiyah6Kab. Malang. Ofeachelementary schoo lteacher involves one personstartedgrades 4-6.Eachteacherwhobecamea traineegetreinforcementof concepts andthematiclearning materialsinthe workshop. Furthermore, thestrengthening ofmentoringas the embodiment ofthe concept ofthematic learningobtainedin thepreviousactivity. Of thementoring activitiesgenerated6netstheme, 6Syllabus, and6RPPeachofthe participantsgrades 4-6. The resultsofsuchassistancethendopeer teachingand reviewandreflection onthe resulting product. The resultsof thepeerreview and reflectionof teachingas well asin the form of3sets ofnetstheme, lesson plansandsyllabithematic learning.Eachgrade4-6obtained1 setnetstheme, lesson plansandsyllabithematic learning. Overall, the activitieshave been conductedandthe resultshave beenobtainedin accordancewith theplanningresults.